FORMULASI DAN UJI MUTU FISIK KRIM MASKER WAJAH ANTI-AGING FRAKSI DAUN MIANA (Coleus scutellarioides (L) Benth) - Silaban Erllin Tirza Stevany; Muh. Taufiqurrahman; Nurillahi Febria Leswana (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
One of the natural ingredients that can be used as a cosmetic ingredient is miana leaf (Coleus scutelleroides (L) Benth) which contains flavonoid compounds with antioxidant activity that can be used for skin care. These compounds can prevent free radicals that can cause premature aging. The extraction method was used in this study with 96% ethanol solvent and continued with the fractionation process. The determination of antioxidant activity was determined by calculating the IC50 value where the IC50 value of the ethyl acetate fraction of miana leaves obtained was 27.90 ppm. In the study, a formulation of face mask cream preparations with a variety of active ingredients (0,6; 1,2; 2,4). Evaluation of the preparation was carried out on the physical quality of face mask cream using the cycling test method. Based on the results of stability tests on the four preparations, formula 2 with 1.2 g of active ingredients shows the best formula. Antioxidant testing from F1, F2 and F3 obtained IC50 values of 96.33 ppm, 82.73 ppm, 72.71 ppm. The statistical test of antioxidant activity showed a p<0.05 result which indicates that there is a significant difference between the three formulas. Cycling test showed that the facial mask cream preparation was physically and chemically stable. There was no significant change in color, odor, texture, phase separation, or pH change. Viscosity also remained stable, indicating good shelf life during normal storage.